KEMAMPUAN MANAJERIAL KEPALA SEKOLAH BERBASIS ADAT BUDAYA TAMIANG DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH DASAR KABUPATEN ACEH TAMIANG - Roi Susanti; Iskandar Iskandar; Hera Yanti (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to analyze (1) technical skills, (2) interpersonal skills, and (3) conceptual skills of principals based on the local wisdom of Tamiang Traditional Culture (Adat Budaya Tamiang/ABT) in improving teacher performance in elementary schools of Aceh Tamiang Regency. This research employed a qualitative method with a case study approach. The research subjects consisted of principals, teachers, and representatives of the Aceh Tamiang Traditional Council (MAA) from two schools, namely SD Negeri 1 Sungai Liput and SD Negeri 1 Sriwijaya. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that: (1) The principals technical skills were reflected in their ability to formulate and manage RKS and RKAS through deliberation, integrate ABT into the curriculum, utilize internet-based learning media, provide cultural literacy resources such as the Tamiang language dictionary, and manage school facilities through the spirit of gotong royong (collective work). These programs contributed to improving teacher performance through clear planning, facility support, and work guidelines rooted in local wisdom. (2) Interpersonal skills were demonstrated through polite and ethical communication based on Tamiang customs, conflict resolution using a familial and consensus approach, teacher empowerment through kelompok belajar (teacher learning groups), participatory practices, and the creation of a collaborative work climate. This approach enhanced teacher motivation, commitment, and discipline. (3) Conceptual skills were evident in the principals' ability to formulate a vision and mission grounded in Tamiang cultural values, adapt national education policies to the local context, build solid teamwork, conduct data-based evaluations (including school performance reports, BOS Kinerja achievements, and “Beautiful Classroom” assessments), and involve communities and traditional institutions in school programs, including traditions such as pesejuk and the use of Malay Tamiang traditional attire. This study concludes that the managerial abilities of school principals based on the local wisdom of Tamiang cultural values significantly contribute to improving teacher performance through the application of technical, interpersonal, and conceptual skills rooted in local traditions. Principals are able to plan programs through deliberation, build harmonious working relationships, and interpret educational policies in accordance with the Tamiang cultural context. The integration of values such as togetherness, mutual cooperation, and social responsibility strengthens teachers' professionalism while fostering students' character and cultural identity.